KEPEMIMPINAN GUNA MEMBANGUN TIM KERJA DI LEMBAGA PENDIDIKAN ISLAM - Sri Putrianingsih; Sulistyorini (Center for the Research and the Communicator Service of IAI Hasanuddin Pare-Kediri, 2023)
Abstract Leadership in building a team at an islamic education is very impotant, because through solid leadership at is able to awaken motivation for members of the work in creating superior, high-quality education. Leadership is an interaction of group members aimed at creating change, renewal, and changing motivation to bring about a collective decision. These elements are human resources made up of schollteachers, educators, staff, learners, of students, and student parents. Leadership is an important part of the manajement of planning, organizing, but the main role of leadershio is to influence others to actieve the astablisted goals. Leadership has been described as a job adjustment through the person or group an manager’s performance will depend on his her ability as manager in an organization leader. this means leaders are able to influence the subordinates or members of the organization to achieve the desired and mutually establisted results in an organization. key word : leadership, the team work